Teaching practices, work environment, and professional attitudes in the Moroccan educational context: evidence from a document analysis - BIYOUDA Samir,; ACHNID Jaouad, (African Scientific Journal, 2026)
Abstract Teaching practice constitutes a central lever for the transformation of educational systems, as it is constructed at the intersection of institutional prescriptions, organizational constraints, and psychosocial dynamics. In the Moroccan context, marked by successive reforms such as the National Charter for Education and Training, the Emergency Program, and the Framework Law No. 51‑17, which operationalized the Strategic Vision 2015–2030, teachers are explicitly positioned as strategic actors in improving the quality of education. However, the actual conditions under which the profession is practiced reveal the persistence of structural and organizational constraints that may influence pedagogical practices and professional commitment. This article proposes a theoretical and descriptive analysis of teaching practice in Morocco through an articulated examination of two complementary dimensions: the work environment and professional attitudes. The research adopts a document analysis approach, drawing on national policy documents, institutional reports, and international scientific literature to provide a comprehensive understanding of teachers’ working conditions and professional attitudes within the Moroccan education system. The research argues that understanding pedagogical practices and the performance of the Moroccan education system requires an integrated reading of organizational contexts and teachers’ professional dispositions. By providing an analytical synthesis of existing studies, it contributes to informing academic and institutional debates on the sustainable improvement of the Moroccan school system. Keywords - Moroccan education system; Teaching practices; Work environment; Professional attitudes.